Indigenous Land Philosophy as a Foundation for Patriotic Character: Lessons from Indonesia's Cultural Heritage - Lukuaka, Defrida Suzana; Alexandra, Halomoan Freddy Sitinjak; Saragih, Herlina Juni Risma; Widodo, Pujo (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
The land philosophy embraced by indigenous communities fundamentally represents a microcosm of patriotic character. When discussing ancestral land philosophy, indigenous communities demonstrate profound reverence for inherited land, perceiving it as a living entity or maternal figure that embodies values of loyalty and filial piety. This perspective fosters responsible attitudes toward environmental conservation, as land is viewed as a living being that requires protection. Indigenous land philosophy places strong emphasis on intergenerational responsibility to preserve land for future descendants. This aligns with efforts to maintain national cultural heritage through the preservation of ancestral land values. The concept of communal land ownership within indigenous communities also reflects values of unity and mutual cooperation that form the foundation of communal life. The profound connection to homeland represents a shared emphasis in both indigenous land philosophy and patriotic spirit. Indonesia's independence struggle history has demonstrated how threats to ancestral land sovereignty can ignite patriotic resistance. This study utilizes qualitative literature review with systematic content analysis. Data was collected from academic sources including books and journal articles relevant to the research topic, This reflects a holistic approach to national loyalty and identity, where connection to land transcends physical boundaries to include spiritual and cultural dimensions, forming a robust foundation for authentic and sustainable love of country. The indigenous perspective on land thus provides valuable insights into how traditional wisdom can inform and enrich contemporary understandings of patriotism and national identity.